Construction of Educational Management Software Design Pattern Based on Deep Neural Network - Zi, Ye (Procedia computer science, 2022)
With the popularization of information technology and network in schools and education management departments, the whole school management model based on campus network has become the mainstream of the development of education management information system. Relying on the theoretical basis of the information management system MS, the system application platform designed and developed for the teaching management of colleges and universities can assist the staff to efficiently process various kinds of information in the school and provide information services for the teachers and students of the whole school. Deep learning under steam education means that students, under the guidance of teachers, actively, joyfully and interactively participate in teaching activities around challenging, integrated and ideological topics, realize the understanding, connection and transfer of knowledge on the basis of original experience, and apply it to problem solving in real situations, so as to finally form a critical and creative high-level thinking ability. In view of the shortcomings of the traditional course push model algorithm, this paper combines the multi-layer neuron model algorithm with the personalized recommendation algorithm, and verifies the course data.